Aflatoxin-Induced TP53 R249S Mutation in HepatoCellular Carcinoma in Thailand: Association with Tumors Developing in the Absence of Liver Cirrhosis - Villar, Stephanie; Ortiz-Cuaran, Sandra; Abedi-Ardekani, Behnoush; Gouas, Doriane; Nogueira da Costa, Andre; Plymoth, Amelie; Khuhaprema, Thiravud; Kalalak, Anant; Sangrajrang, Suleeporn; Friesen, Marlin D.; Groopman, John D.; Hainaut, Pierre (PLOS ONE, 2012)
Primary Liver Cancer (PLC) is the leading cause of death by cancer among males in Thailand and the 3rd among females. Most cases are hepatocellular carcinoma (HCC) but cholangiocarcinomas represent between 4 and 80% of liver cancers depending upon geographic area. Most HCC are associated with chronic infection by Hepatitis B Virus while a G→T mutation at codon 249 of the TP53 gene, R249S, specific for exposure to aflatoxin, is detected in tumors for up to 30% of cases. We have used Short Oligonucleotide Mass Analysis (SOMA) to quantify free circulating R249S-mutated DNA in plasma using blood specimens collected in a hospital case:control study. Plasma R249S-mutated DNA was detectable at low concentrations (≥67 copies/mL) in 53 to 64% of patients with primary liver cancer or chronic liver disease and in 19% of controls. 44% of patients with HCC and no evidence of cirrhosis had plasma concentrations of R249S-mutated DNA ≥150 copies/mL, compared to 21% in patients with both HCC and cirrhosis, 22% in patients with cholangiocarcinoma, 12% in patients with non-cancer chronic liver disease and 3% of subjects in the reference group. Thus, plasma concentrations of R249S-mutated DNA ≥150 copies/mL tended to be more common in patients with HCC developing without pre-existing cirrhosis (p = 0.027). Overall, these results support the preferential occurrence of R249S-mutated DNA in HCC developing in the absence of cirrhosis in a context of HBV chronic infection.